IMPROVEMENT OF ALOPECIA AND DECREASES IN HAIR CORTISOL AND DIHYDROTESTOSTERONE CONCENTRATIONS AFTER THE TOPICAL USE OF PLANT EXTRACTS IN MEN WITH ANDROGENETIC ALOPECIA - DO, SANG-HWAN; AHN, RYUN-SUP; NA, MYUNG-SUK; JU, HYUNG-RUEL (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Plant extracts possessing specific constituents with anti-inflammatory, antimicrobial, antioxidant, or 5α-reductase inhibitory properties are known to provide benefits against androgenetic alopecia (AGA) in men. A solid shampoo was formulated, and it contained a mixture of six different plant extracts that possess these beneficial properties against AGA. The improvement in AGA and changes in steroid concentrations were assessed after 4 months of formulated shampoo use. Methods: This study was conducted based on a randomized, placebo-controlled, and single-blind design. Hair-related variables and hair and saliva samples were collected bi-monthly in the treatment (n=48) and placebo (n=52) groups and at a single time point in the hairy controls (n=50). Results: The formulated shampoo was more effective on AGA than the placebo based on the hair shaft thickness and hair density in the receding hairline. The baseline hair cortisol and dihydrotestosterone (DHT) concentrations were significantly higher in the treatment and placebo groups than in the hairy controls. After 4 months, the hair steroid concentrations in the treatment group were reduced to those observed in the hairy controls, although the main effect of time on hair steroid concentrations was negligible in the placebo group. Salivary cortisol and DHT levels during the post-awakening period were comparable among the groups or assessment time points. Conclusion: The constituents of plant extracts included in the formulated shampoo would prevent hair loss, increase hair growth effects, and reduce hair cortisol and DHT concentrations without changes in the post-awakening salivary steroid levels in men with AGA.